2018
DOI: 10.1017/s0022215118002049
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bidi smoking on nasal mucociliary clearance: a comparative study

Abstract: ObjectiveTo compare nasal mucociliary clearance in adult non-smokers, cigarette smokers and bidi smokers using the methylene blue dye test.MethodsThe study sample consisted of 20 non-smokers, 20 cigarette smokers and 20 bidi smokers (age range, 20–40 years). A single drop of the methylene blue dye was placed at the anterior end of the inferior turbinate of the participants’ nasal cavity. The distance travelled by the methylene blue in 15 minutes inside the nasal cavity was measured. Nasal mucociliary clearance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…7,29,38 Bidi is a hand-rolled tobacco product, and, unlike cigarettes, it is devoid of a filter (the filter of a cigarette functions as a barrier, by preventing the noxious smokes from reaching the nasal cavity). 3,39 Although a bidi contains a lower amount of tobacco compared with a cigarette, it produces higher levels of noxious susbtances like nicotine, carbon monoxide, tar, phenols, and ammonia and results in a higher degree of impairment and addiction. 3,40 It has been reported that bidi produces three times the amount of carbon monoxide and nicotine, and five times the amount of tar than cigarettes.…”
Section: Xavier Et Al 2013 20mentioning
confidence: 99%
See 4 more Smart Citations
“…7,29,38 Bidi is a hand-rolled tobacco product, and, unlike cigarettes, it is devoid of a filter (the filter of a cigarette functions as a barrier, by preventing the noxious smokes from reaching the nasal cavity). 3,39 Although a bidi contains a lower amount of tobacco compared with a cigarette, it produces higher levels of noxious susbtances like nicotine, carbon monoxide, tar, phenols, and ammonia and results in a higher degree of impairment and addiction. 3,40 It has been reported that bidi produces three times the amount of carbon monoxide and nicotine, and five times the amount of tar than cigarettes.…”
Section: Xavier Et Al 2013 20mentioning
confidence: 99%
“…3,39 Although a bidi contains a lower amount of tobacco compared with a cigarette, it produces higher levels of noxious susbtances like nicotine, carbon monoxide, tar, phenols, and ammonia and results in a higher degree of impairment and addiction. 3,40 It has been reported that bidi produces three times the amount of carbon monoxide and nicotine, and five times the amount of tar than cigarettes. Given the low combustibility of the tendu leaf wrapper, bidi smokers must take more frequent and deeper puffs, resulting in the inhalation of more smoke, which is disseminated deeper into the lungs.…”
Section: Xavier Et Al 2013 20mentioning
confidence: 99%
See 3 more Smart Citations